2007
DOI: 10.1002/chem.200701317
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Approach to Geminal Bisphosphonates by Organocatalyzed Michael‐Type Addition of β‐Ketoesters

Abstract: A valuable organocatalyzed protocol has been developed for the asymmetric synthesis of bisphosphonate derivatives, a class of pharmaceutically important molecules. Cheap and commercially available dihydroquinine effectively catalyzed conjugate additions of cyclic beta-ketoesters to ethylidenebisphosphonate esters, leading to optically active geminal bisphosphonates, bearing an all-carbon substituted quaternary stereocenter, in high yields and enantioselectivities of up to 99 % ee. Further elaborations of Micha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…More rare are enantioselective preparations of 2,2′-disubstituted benzofuranones. In 2008, Jørgensen and coworkers reported that 2-tert-butoxy carbonyl benzofuranone could be alkylated asymmetrically with tetraethyl ethylidene-bisphosphonate to give the corresponding 2,2′-disubstituted product in excellent enantioselectivity (44). In a different approach, we have shown that chiral triazolinylidene carbenes mediate the cyclization of aldehyde-tethered, β,β-disubstituted Michael acceptors related to 12 to give benzofuranone products in excellent enantioselectivities (Scheme 2) (45-47).…”
mentioning
confidence: 92%
“…More rare are enantioselective preparations of 2,2′-disubstituted benzofuranones. In 2008, Jørgensen and coworkers reported that 2-tert-butoxy carbonyl benzofuranone could be alkylated asymmetrically with tetraethyl ethylidene-bisphosphonate to give the corresponding 2,2′-disubstituted product in excellent enantioselectivity (44). In a different approach, we have shown that chiral triazolinylidene carbenes mediate the cyclization of aldehyde-tethered, β,β-disubstituted Michael acceptors related to 12 to give benzofuranone products in excellent enantioselectivities (Scheme 2) (45-47).…”
mentioning
confidence: 92%
“…Catalysts 2017, 7, 90 2 of 10 where very few examples have been reported in the literature [11][12][13], with only one example of an enantioenriched BP having been biologically tested, observing a 24-fold difference in activity between the enantiomers [14]. This situation reflects the problems of dealing synthetically with molecules having a bisphosphonate group which induces (i) a strong electrophilicity on the central C atom and eventually on adjacent moieties; (ii) a significant steric hindrance leading in many cases to limited accessibility and poor reactivity; and (iii) the capacity of strongly binding metal ions, thereby inactivating catalysts in transition metal-catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52] The fourth work deals with chiral base-catalyzed Michael addition of bketoA C H T U N G T R E N N U N G esters. [53] In 2007 Alexakis et al reported that in the presence of 86 a various aldehydes 106 can be added to tetraethyl methylidenebisphosphonate 107 a in a highly asymmetric fashion leading to the formation of geminal bisphosphonates 108 (Scheme 29). [50] The Michael adducts were further converted into functionalized vinylphosphonates with conservation of optical purity achieved in the Michael addition step.…”
Section: Vinylphosphonates In Asymmetric Organocatalysismentioning
confidence: 98%
“…Four examples of asymmetric, organocatalytic A C H T U N G T R E N N U N G Michael addition to activated vinylphosphonates can be found in the literature. [50][51][52][53] Three of them apply the Michael addition of unmodified aldehydes or ketones catalyzed by chiral secondary amines for the formation of the corresponding enamine in the catalytic cycle. [50][51][52] The fourth work deals with chiral base-catalyzed Michael addition of bketoA C H T U N G T R E N N U N G esters.…”
Section: Vinylphosphonates In Asymmetric Organocatalysismentioning
confidence: 99%